Povyšenie rezul'tativnosti štrafnych broskov basketbolistok studenceskoj komandy - Yavorskaya, E. E.; Dyachenko, Yu. A.; Rodionova, A. G. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The article is devoted to the problem of realization of free throws from female students-basketball players. Identified the main reasons that affect the reduction in the effectiveness of the execution of free throws in official competitions. Efficient tools and methods are selected that allow novice players to master the perfect technique of free throw, and qualified - to improve the technique in varying conditions of the game situation. Recommendations are presented to increase the effectiveness of free throws in conditions of training and competitive activities, taking into account the qualifications of the students of the student team.